H-EARtH: Heterogeneous Multicore Platform Energy Management. - Rotem, Efraim; Weiser, Uri C.; Mendelson, Avi; Ginosar, Ran; Weissmann, Eliezer; Aizik, Yoni (Computer (00189162), 2016)
By scheduling each workload according to its most advantageous core and managing voltage and frequency, the heterogeneous energy-aware race to halt (H-EARtH) algorithm optimizes CPU platform energy.